Penerapan Model Collaborative Governance Dalam Pelaksanaan Program Vaksin COVID-19 Pada Sentra Vaksinasi Masjid Salman ITB - Resty Nurdiantika Ramadhanti; Wawan Setiawan Abdillah; Abdal Abdal (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2022)
In March 2020, there are various countries in the world were appaled by the Covid-19 virus, including Indonesia. At ten months intervals, in January 2021 the Indonesian government finally started a vaccine program, to speed it up, vaccine centers were created in each area. In the city of Bandung itself, the local government accentuate collaboration in efforts to cope the pandemic. Therefore, the Bandung City Health Service, YPM Salman ITB, and the society work together in a collaboration to set up the ITB Mosque Vaccine Center which also indirectly applies the Collaborative Governance model in its implementation. Collaborative Governance is a strategy model which the government involves stakeholders from the outside of government itself in solving public problems. However, the application of the Collaborative Governance model in this vaccine program still needs to be researched further, therefore the researchers are interested in taking this topic to find out how the Collaborative Governance model is applied in the vaccine program that took place at the Salman Mosque Vaccination Center, ITB. This research uses a qualitative descriptive method with data collection techniques through interviews and literature studies. The theory used in this research refers to the opinion of Ansell & Gash which propose that there are four variables that need to be considered in the practice of collaborative governance, specifically: 1) Starting Conditions; 2) Institutional Design; 3) Facilitative Leadership; and 4) The Collaborative Process. In that implementation, the collaboration that was carried out went smoothly smoothly and could be said to be optimal based on the Ansell & Gash criteria. This is also because each stakeholder has adequate capacity and resources, along with understands their respective tasks and roles so that the Salman Mosque Vaccine Center ITB can be managed properly.Keywords: Collaborative Governance, Collaboration, Program, Vaccine Center, Covid-19